Investigation of Shear Complex Modulus and Phase Angle Values of Short- and Long-term Aged Polymer Modified Bitumens at Different Frequencies - Alatas, Taner; Yilmaz, Mesude; Kuloglu, Necati; Cakiroglu, Mehmet; Geckil, Tacettin (Korean Society of Civil Engineers-Ksce, 2014)
In this study, modified bitumens were prepared by mixing two types of Styrene-Butadiene-Styrene (SBS-D and SBS-M) and Ethylene-Vinyl-Acetate (EVA) with B 160/220 base bitumen 3% by weight. The short- and long-term aging processes were applied to base and modified binders with rolling thin film oven test and pressure aging vessel, respectively. Dynamic Shear Rheometer (DSR) test conducted at different temperatures and frequencies showed that while the shear complex modulus (G*) of unaged, short- and long-term aged binders reduced, the phase angle (delta) of those increased. The shear complex modulus values increased and the phase angle values decreased by the effect of aging and increase in frequency. The G*/sin delta values increased with the addition of modifiers to the base bitumen. Comparison of modifiers demonstrated that the effective modifier type shows variety according to frequency, temperature and aging conditions.
Keywords: bitumen; modification; aging; styrene-butadiene-styrene; ethylene-vinyl-acetate